Microbial immigration in full-scale activated sludge systems is influenced by operational and design parameters - Ramis Rafay; S Jane Fowler (Water Research, 2026)

Past, present and future of the indus water treaty: implications for transboundary water governance challenges and modernization prospects - Tejal S. Shirsat; Lara B. Fowler; Christopher A. Scott (Water Security, 2026)

Closure of the Strait of Hormuz may trigger a bioinvasion super-spreader event - Mario N. Tamburri; James T. Carlton; April M. H. Blakeslee; Alejandro Bortolus; João Canning-Clode; Susana Carvalho; Andrew L. Chang; Ian C. Davidson; Sarah C. Donelan; Lisa A. Drake; Amy E. Fowler; Amy L. Freestone; et al. (Biological Invasions, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Rapid Quantification of Bacteriophages of Mycobacterium spp. and Related Genera in Aquatic Systems - Hanieh Shakeri Moghaddam; S. Jane Fowler (Environmental Microbiology, 2026)
Viruses shape microbial communities but remain underexplored in aquatic systems. Most studies target specific viruses as contamination indicators, while the potential of phages to reflect microbial dynamics is often overlooked. We designed and optimised two qPCR assays to quantify specific phages from the order Caudoviricetes —some of the most abundant in aquatic environments—infecting Mycobacterium , Rhodococcus and Gordonia spp. Major capsid protein (MCP) sequences were retrieved from the NCBI Viral Database and degenerate and non‐degenerate primers, along with a TaqMan probe, were developed targeting the MCP gene. SYBR Green and TaqMan assays were optimised, validated using an MCP sequence and applied to samples from a drinking water treatment plant (DWTP), urban lakes and activated sludge. Both assays showed strong linearity with efficiencies of 95% (TaqMan) and 94% (SYBR Green). Viral gene copies decreased across the DWTP, indicating up to four‐log phage removal during treatment. Phage counts in source water paralleled bacterial counts, especially in the cold season, suggesting a potential correlation between phages and bacterial hosts. Lake samples had higher phage concentrations (up to 10 6 copies/L), while only two wastewater treatment plants showed phage presence. These assays offer sensitive tools for monitoring phage abundance and microbial dynamics in freshwater environments.

Developing a radar-rain gauge hourly blended precipitation dataset for Great Britain using the Gauss Blending Method - X. Qiu; A.C. Green; S. Blenkinsop; H.J. Fowler (Journal of Hydrology, 2026)

Quality control of the composite radar quantitative precipitation estimation product for Great Britain - X. Qiu; A.C. Green; S. Blenkinsop; H.J. Fowler (Journal of Hydrology, 2026)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Remote sensing, petrogenesis and tectono-magmatic evolution of the Wadi Queh-Wadi Abu Shigeili area: a window into the transitional history of the central Egyptian-Nubian Shield from pre-plate collision to post-collision magmatism - Osama K. Dessouky; El-Sayed H. El-Sawey; Yasser S. Badr; Sobhi Nasir; Gehad M. Saleh; Ahmed M. Dardier; Kamal A. Ali; Abdel-Rahman Fowler; Saleh E. Ammar; Ahmed M. Ismail; Mahmoud M. Hassan (International Journal of Earth Sciences, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Identifying capacity limitations and training needs using a stock assessment game - André E. Punt; Catherine M. Dichmont; Natalie A. Dowling; Roy A. Deng; Sean Pascoe; Ingrid van Putten; Pia Bessell-Browne; Paul Burch; Owen Burnell; Rowan C. Chick; Simon de Lestang; Ainslie Denham; et al. (Fisheries Research, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Biodegradation behavior of wool and other textile fibers in aerobic composting conditions - S. Collie; P. Brorens; M. Hassan; I. Fowler (International Journal of Environmental Science and Technology, 2025)
Pollution of the environment by microscopic fragments of plastic is a growing environmental concern. A category of this pollution is fiber fragments from textiles, a source of which is believed to be fibers released by clothing made of synthetic fibers during laundering. These fragments could enter the environment at the end of the textile’s useful life if it is not re-used or recycled. Disposal of biodegradable fibers could be achieved by industrial composting, but natural fibers are sometimes modified during manufacturing in ways that might influence biodegradation. The composting behavior of fabrics made with unmodified and chemically modified wool fibers (chlorine-Hercosett treated), regenerated cellulose, and several synthetic fibers was compared in industrial composting conditions according to an established standard test method. The fabrics were characterized by Fourier transform infrared spectroscopy, energy dispersive X-ray and electron microscopy. The regenerated cellulose (viscose rayon) biodegraded to the greatest extent in the test, and both types of wool also biodegraded readily. All three synthetic fibers had no biodegradation. The machine-washable wool biodegraded more rapidly than unmodified wool and analysis of residues at the conclusion of the test indicated that it did not generate non-degradable fiber fragments. The epicuticle of unmodified wool is covered with a hydrophobic layer, which may resist microbial attack, but with time this slowly degraded. Conversely, the machine-washable wool is hydrophilic and therefore was easier for microbes to attack. If not re-used, commercial, machine-washable wool textiles can be readily disposed of in industrial composting conditions.

Household Food Sourcing Patterns and Their Associations With Food Insecurity in Appalachian Ohio - Kyle R. Busse; Kathryn I. Poppe; Qiang Wu; Stephanie B. Jilcott Pitts; Lindsey Haynes-Maslow; Alice S. Ammerman; Kathleen Krzyzanowski Guerra; Zoë Plakias; Andrew S. Hanks; Katharine Garrity; Rachel Gillespie; Bailey Houghtaling; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Magnetosonic waves in the Martian ionosphere driven by upstream proton cyclotron waves: Two-point observations by MAVEN and Mars Express - K. Imada; Y. Harada; C.M. Fowler; G. Collinson; J.S. Halekas; S. Ruhunusiri; G.A. DiBraccio; N. Romanelli (Icarus, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Making waves: From tap to gut- exploring the impact of drinking water on gut microbiota - Hanieh Shakeri Moghaddam; Leili Abkar; S. Jane Fowler (Water Research, 2024)

Children’s exposure to chemical contaminants: Demographic disparities and associations with the developing basal ganglia - Carina H. Fowler; Aaron Reuben; Heather M. Stapleton; Kate Hoffman; Nicholas Herkert; Lubna Barakat; Michael S. Gaffrey (Environmental Research, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Microbial ecology of drinking water from source to tap - Leili Abkar; Hanieh Shakeri Moghaddam; S. Jane Fowler (Science of The Total Environment, 2024)

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

P16-30: Examining the need for an ovarian-specific steroidogenic assay to prioritize potential endocrine disrupting chemicals - P. Vazakidou; T. Li; L.L. Lecante; S. Mazaud-Guittot; P.A. Fowler; P. Damdimopoulou; P. Leonards; M. van Duursen (Toxicology Letters, 2023)

P08-11: Characterisation of the effects of Ketoconazole on the human fetal adrenal - L.L. Lecante; P. Vazakidou; P. Lelandais; P. Liu; M. van Duursen; S. Mazaud-Guittot; P.A. Fowler (Toxicology Letters, 2023)

Fruit and Vegetable Preparation Changes During and After Cost-Offset Community-Supported Agriculture Plus Nutrition Education - Grace A. Marshall; Jennifer A. Garner; Karla L. Hanson; Alice S. Ammerman; Stephanie B. Jilcott Pitts; Jane Kolodinsky; Marilyn Sitaker; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2023)

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Conservation of endangered galaxiid fishes in the Falkland Islands requires urgent action on invasive brown trout - J. F. Minett; D. M. Fowler; J. A. H. Jones; P. Brickle; G. T. Crossin; S. Consuegra; C. Garcia de Leaniz (Biological Invasions, 2023)
Non-native salmonids are protected in the Southern hemisphere where they sustain aquaculture and lucrative sport fisheries, but also impact many native fishes, which poses a conservation conundrum. Legal protection and human-assisted secondary releases may have helped salmonids to spread, but this has seldom been tested. We reconstructed the introduction of brown trout ( Salmo trutta ) to the Falkland Islands using historical records and modelled its dispersal and probability of invasion using a generalized linear model and Leave One out Cross Validation. Our results indicate that establishment success was ~ 88%, and that dispersal was facilitated over land by proximity to invaded sites and density of stream-road crossings, suggesting it was human assisted. Brown trout have already invaded 54% of Falkland rivers, which are 2.9–4.5 times less likely to contain native galaxiids than uninvaded streams. Without strong containment we predict brown trout will invade nearly all suitable freshwater habitats in the Falklands within the next ~ 70 years, which might put native freshwater fishes at a high risk of extinction.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Use of plastid genome sequences in phylogeographic studies of tree species can be misleading without comprehensive sampling of co-occurring, related species - Patrick S. Fahey; Rachael M. Fowler; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Tree Genetics & Genomes, 2021)

Pharmacokinetic and pharmacodynamic properties of aerosolized (“vaped”) THC in adolescent male and female rats - C. M. Ruiz; A. Torrens; V. Lallai; E. Castillo; L. Manca; M. X. Martinez; D. N. Justeson; C. D. Fowler; D. Piomelli; S. V. Mahler (Psychopharmacology, 2021)

Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar - Fatma Ben Abid; Clement K. M. Tsui; Yohei Doi; Anand Deshmukh; Christi L. McElheny; William C. Bachman; Erin L. Fowler; Ahmed Albishawi; Kamran Mushtaq; Emad B. Ibrahim; Sanjay H. Doiphode; Manal M. Hamed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). bla NDM-1 (45; 30.2%) and bla OXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identified in 5 (3.6%) isolates. Most common sequence types were E. coli ST410 (8; 21.1%) and ST38 (7; 18.4%), and K. pneumoniae ST147 (13; 16%) and ST231 (7; 8.6%).

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Increased expression of plasminogen activator inhibitor-1 (PAI-1) is associated with depression and depressive phenotype in C57Bl/6J mice - René A. Girard; Prashant S. Chauhan; Torry A. Tucker; Tim Allen; Jaswinder Kaur; Ann Jeffers; Kathleen Koenig; Galina Florova; Andrey A. Komissarov; Tatiana A. Gaidenko; Mignote B. Chamiso; James Fowler; et al. (Experimental Brain Research, 2019)

Recruitment and facilitation in Pinus hartwegii, a Mexican alpine treeline ecotone, with potential responses to climate warming - Claudia C. Astudillo-Sánchez; Mike S. Fowler; José Villanueva-Díaz; Angel R. Endara-Agramont; Leroy Soria-Díaz (Trees, 2019)

Functional diversity of predators and parasitoids does not explain aphid biocontrol efficiency - Sanaa N. Alhadidi; Mike S. Fowler; John N. Griffin (BioControl, 2019)

Primary central nervous system lymphoma in patients with and without HIV infection: a multicenter study and comparison with U.S national data - Dima Dandachi; Quinn T. Ostrom; Insun Chong; Jose A. Serpa; Thomas P. Giordano; Carol Kruchko; Jill S. Barnholtz-Sloan; Nathan Fowler; Rivka R. Colen; Fanny E. Morón (Cancer Causes & Control, 2019)

The status of the invertebrate fauna on the South Atlantic island of St Helena: problems, analysis, and recommendations - Alan Gray; Vicky Wilkins; David Pryce; Liza Fowler; Roger S. Key; Howard Mendel; Michael Jervois; Axel Hochkirch; Rebecca Cairns-Wicks; Amy-Jayne Dutton; Lourens Malan (Biodiversity and Conservation, 2019)

The colour of environmental fluctuations associated with terrestrial animal population dynamics - David Gilljam; Jonas Knape; Andreas Lindén; Marianne Mugabo; Steven M. Sait; Mike S. Fowler (Global Ecology and Biogeography, 2019)
Aim The temporal structure (colour) of environmental variation influences population fluctuations, extinction risk and community stability. However, it is unclear whether environmental covariates linked to population fluctuations are distinguishable from a purely random process (white noise). We aimed to estimate colour coefficients and relative support for three models commonly representing coloured stochastic processes, in environmental series linked to terrestrial animal population fluctuations. Location North America and Eurasia. Time period 1901–2002. Major taxa studied Birds, insects and mammals. Methods We analysed multiple abiotic environmental covariates, comparing point estimates and confidence intervals of temporal structure in competing models fitted using white noise, autoregressive [AR(1)] and 1/ f processes in the time domain and the frequency domain (where time series were analysed after decomposition into different sinusoidal frequencies and their relative powers). All animal time series were sampled annually for ≤ 50 years, potentially inflating type II errors. We also considered 101‐year series of matched environmental covariates, performing a statistical power analysis evaluating our ability to draw robust conclusions. Results Temperature‐related variables were associated with the largest fraction of population fluctuations. Ninety‐three per cent of shorter environmental series were indistinguishable from white noise, limited by time‐series length and associated with wide confidence intervals. The longer environmental series analysed in the time domain offered sufficiently high statistical power to identify correctly colour estimates ≥ |0.27|, indicating that 20% of series were best described by a slightly reddened noise process. Main conclusions Focusing on the short time‐scales typically available for ecologists, most environmental variables associated with terrestrial animal population fluctuations are best characterized by white noise processes, although type II errors are common. The correct detection of intermediately coloured noise with power 0.8 requires ≥ 16 data points in the time domain or ≥ 47 points in the frequency domain. Over longer time‐scales, where type II errors are less likely, one‐fifth of populations are associated with coloured (often reddened) variables.

Optimising physiochemical control of invasive Japanese knotweed - Daniel Jones; Gareth Bruce; Mike S. Fowler; Rhyan Law-Cooper; Ian Graham; Alan Abel; F. Alayne Street-Perrott; Daniel Eastwood (Biological Invasions, 2018)
Japanese knotweed, Fallopia japonica var. japonica , causes significant disruption to natural and managed habitats, and provides a model for the control of invasive rhizome-forming species. The socioeconomic impacts of the management of, or failure to manage, Japanese knotweed are enormous, annually costing hundreds of millions of pounds sterling (GBP£) in the UK alone. Our study describes the most extensive field-based assessment of F. japonica control treatments undertaken, testing the largest number of physical and/or chemical control treatments (19 in total) in replicated 225 m 2 plots over 3 years. Treatments focused on phenology, resource allocation and rhizome source–sink relationships to reduce the ecological impacts of controlling F. japonica . While no treatment completely eradicated F. japonica, a multiple-stage glyphosate-based treatment approach provided greatest control. Increasing herbicide dose did not improve knotweed control, but treatments that maximised glyphosate coverage, e.g., spraying versus stem injection, and exploited phenological changes in rhizome source–sink relationships caused the greatest reduction of basal cover and stem density after 3 years. When designing management strategies, effective control of F. japonica may be achieved by biannual (summer and autumn) foliar glyphosate applications at 2.16 kg AE ha −1 , or by annual application of glyphosate in autumn using stem injection at 65.00 kg AE ha −1 or foliar spray at 3.60 kg AE ha −1 . Addition of other herbicides or physical treatment methods does not improve control. This work demonstrates that considering phenology, resource allocation and rhizome source–sink relationships is critical for the control of invasive, rhizome forming species.

Natural enemy composition rather than richness determines pest suppression - Sanaa N. Alhadidi; John N. Griffin; Mike S. Fowler (BioControl, 2018)

Temperature‐extreme precipitation scaling: a two‐way causality? - R. Barbero; S. Westra; G. Lenderink; H. J. Fowler (International Journal of Climatology, 2018)
Extreme precipitation events are widely thought to intensify in a warmer atmosphere through the Clausius‐Clapeyron equation. The temperature‐extreme precipitation scaling was proposed to analyse the temperature dependency of short‐duration extreme precipitation and since then, the concept has been widely used in climatology. Bao et al. (2017) suggest that the apparent scaling reflects not only how surface air properties affect extreme precipitation, but also reflects how synoptic conditions and localized cooling due to the storm itself affect the scaling – implying two‐way causality. We address here critical issues of this paper and provide evidence that dew point temperature drives extreme precipitation, with the direction of causality reversed only for the storm's peak intensity. This physical inference may serve as a basis to better quantify scaling rates and to help establish the relationship between extreme precipitation and environmental conditions in the current climate, and thereby provide insights into future changes to precipitation extremes due to climate change.

Top-down and bottom-up control on cougar and its prey in a central Mexican natural reserve - Leroy Soria-Díaz; Mike S. Fowler; Octavio Monroy-Vilchis (European Journal of Wildlife Research, 2017)

Boom‐bust dynamics in biological invasions: towards an improved application of the concept - David L. Strayer; Carla M. D'Antonio; Franz Essl; Mike S. Fowler; Juergen Geist; Sabine Hilt; Ivan Jarić; Klaus Jöhnk; Clive G. Jones; Xavier Lambin; Alexander W. Latzka; Jan Pergl; et al. (Ecology Letters, 2017)
Boom‐bust dynamics – the rise of a population to outbreak levels, followed by a dramatic decline – have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom‐bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom‐bust dynamics and provide specific suggestions for improving the application of the boom‐bust concept. Boom‐bust dynamics can arise from many causes, some closely associated with invasions, but others occurring across a wide range of ecological settings, especially when environmental conditions are changing rapidly. As a result, it is difficult to infer cause or predict future trajectories merely by observing the dynamic. We use tests with simulated data to show that a common metric for detecting and describing boom‐bust dynamics, decline from an observed peak to a subsequent trough, tends to severely overestimate the frequency and severity of busts, and should be used cautiously if at all. We review and test other metrics that are better suited to describe boom‐bust dynamics. Understanding the frequency and importance of boom‐bust dynamics requires empirical studies of large, representative, long‐term data sets that use clear definitions of boom‐bust, appropriate analytical methods, and careful interpretations.

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Pathogenic variation of Pyrenophora teres f. teres in Australia - R. A. Fowler; G. J. Platz; K. L. Bell; S. E. H. Fletcher; J. D. Franckowiak; L. T. Hickey (Australasian Plant Pathology, 2017)

Humanizing the zebrafish liver shifts drug metabolic profiles and improves pharmacokinetics of CYP3A4 substrates - Kar Lai Poon; Xingang Wang; Ashley S. Ng; Wei Huang Goh; Claudia McGinnis; Stephen Fowler; Tom J. Carney; Haishan Wang; Phillip W. Ingham (Archives of Toxicology, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Foraging strategies of a generalist marine predator inhabiting a dynamic environment - E. A. McHuron; P. W. Robinson; S. E. Simmons; C. E. Kuhn; M. Fowler; D. P. Costa (Oecologia, 2016)

Navigating the complexity of ecological stability - Ian Donohue; Helmut Hillebrand; José M. Montoya; Owen L. Petchey; Stuart L. Pimm; Mike S. Fowler; Kevin Healy; Andrew L. Jackson; Miguel Lurgi; Deirdre McClean; Nessa E. O'Connor; Eoin J. O'Gorman; et al. (Ecology Letters, 2016)
Human actions challenge nature in many ways. Ecological responses are ineluctably complex, demanding measures that describe them succinctly. Collectively, these measures encapsulate the overall ‘stability’ of the system. Many international bodies, including the Intergovernmental Science‐Policy Platform on Biodiversity and Ecosystem Services, broadly aspire to maintain or enhance ecological stability. Such bodies frequently use terms pertaining to stability that lack clear definition. Consequently, we cannot measure them and so they disconnect from a large body of theoretical and empirical understanding. We assess the scientific and policy literature and show that this disconnect is one consequence of an inconsistent and one‐dimensional approach that ecologists have taken to both disturbances and stability. This has led to confused communication of the nature of stability and the level of our insight into it. Disturbances and stability are multidimensional. Our understanding of them is not. We have a remarkably poor understanding of the impacts on stability of the characteristics that define many, perhaps all, of the most important elements of global change. We provide recommendations for theoreticians, empiricists and policymakers on how to better integrate the multidimensional nature of ecological stability into their research, policies and actions.

Genomic characterization of sex‐identification markers in Sebastes carnatus and Sebastes chrysomelas rockfishes - Benjamin L. S. Fowler; Vincent P. Buonaccorsi (Molecular Ecology, 2016)
Fish have evolved a variety of sex‐determining (SD) systems including male heterogamy (XY), female heterogamy (ZW) and environmental SD. Little is known about SD mechanisms of Sebastes rockfishes, a highly speciose genus of importance to evolutionary and conservation biology. Here, we characterize the sex determination system in the sympatrically distributed sister species Sebastes chrysomelas and Sebastes carnatus . To identify sex‐specific genotypic markers, double digest restriction site – associated DNA sequencing (ddRAD‐seq) of genomic DNA from 40 sexed individuals of both species was performed. Loci were filtered for presence in all of the individuals of one sex, absence in the other sex and no heterozygosity. Of the 74 965 loci present in all males, 33 male‐specific loci met the criteria in at least one species and 17 in both. Conversely, no female‐specific loci were detected, together providing evidence of an XY sex determination system in both species. When aligned to a draft reference genome from Sebastes aleutianus , 26 sex‐specific loci were interspersed among 1168 loci that were identical between sexes. The nascent Y chromosome averaged 5% divergence from the X chromosome and mapped to reference Sebastes genome scaffolds totalling 6.9Mbp in length. These scaffolds aligned to a single chromosome in three model fish genomes. Read coverage differences were also detected between sex‐specific and autosomal loci. A PCR‐RFLP assay validated the bioinformatic results and correctly identified sex of five additional individuals of known sex. A sex‐determining gene in other teleosts gonadal soma‐derived factor ( gsdf ) was present in the model fish chromosomes that spanned our sex‐specific markers.

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

Latitudinal shifts in coral reef fishes: why some species do and others do not shift - David A Feary; Morgan S Pratchett; Micheal J Emslie; Ashley M Fowler; Will F Figueira; Osmar J Luiz; Yohei Nakamura; David J Booth (Fish and Fisheries, 2014)
Climate change is resulting in rapid poleward shifts in the geographical distribution of many tropical fish species, but it is equally apparent that some fishes are failing to exhibit expected shifts in their geographical distribution. There is still little understanding of the species‐specific traits that may constrain or promote successful establishment of populations in temperate regions. We review the factors likely to affect population establishment, including larval supply, settlement and post‐settlement processes. In addition, we conduct meta‐analyses on existing and new data to examine relationships between species‐specific traits and vagrancy. We show that tropical vagrant species are more likely to originate from high‐latitude populations, while at the demographic level, tropical fish species with large body size, high swimming ability, large size at settlement and pelagic spawning behaviour are more likely to show successful settlement into temperate habitats. We also show that both habitat and food limitation at settlement and within juvenile stages may constrain tropical vagrant communities to those species with medium to low reliance on coral resources.

Changes in the Chlorophyll Content and Cytokinin Levels in the Top Three Leaves of New Plant Type Rice During Grain Filling - Leila Rubia; Latha Rangan; Rimjhim Roy Choudhury; Miroslav Kamínek; Petre Dobrev; Jiri Malbeck; Mark Fowler; Adrian Slater; Nigel Scott; John Bennett; Shaobing Peng; Gurdev S. Khush; et al. (Journal of Plant Growth Regulation, 2014)

Ecological and evolutionary implications of food subsidies from humans - Daniel Oro; Meritxell Genovart; Giacomo Tavecchia; Mike S. Fowler; Alejandro Martínez‐Abraín (Ecology Letters, 2013)
Human activities are the main current driver of global change. From hunter‐gatherers through to Neolithic societies–and particularly in contemporary industrialised countries–humans have (voluntarily or involuntarily) provided other animals with food, often with a high spatio‐temporal predictability. Nowadays, as much as 30–40% of all food produced in Earth is wasted. We argue here that predictable anthropogenic food subsidies ( PAFS ) provided historically by humans to animals has shaped many communities and ecosystems as we see them nowadays. PAFS improve individual fitness triggering population increases of opportunistic species, which may affect communities, food webs and ecosystems by altering processes such as competition, predator–prey interactions and nutrient transfer between biotopes and ecosystems. We also show that PAFS decrease temporal population variability, increase resilience of opportunistic species and reduce community diversity. Recent environmental policies, such as the regulation of dumps or the ban of fishing discards, constitute natural experiments that should improve our understanding of the role of food supply in a range of ecological and evolutionary processes at the ecosystem level. Comparison of subsidised and non‐subsidised ecosystems can help predict changes in diversity and the related ecosystem services that have suffered the impact of other global change agents.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Risk factors for Staphylococcus aureus nasal colonization in Danish middle-aged and elderly twins - P. S. Andersen; L. A. Larsen; V. G. Fowler; M. Stegger; R. L. Skov; K. Christensen (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Genetic epidemiology of cardiometabolic risk factors and their clustering patterns in Mexican American children and adolescents: the SAFARI Study - Sharon P. Fowler; Sobha Puppala; Rector Arya; Geetha Chittoor; Vidya S. Farook; Jennifer Schneider; Roy G. Resendez; Ram Prasad Upadhayay; Jane VandeBerg; Kelly J. Hunt; Benjamin Bradshaw; Eugenio Cersosimo; et al. (Human Genetics, 2013)

Development and characterization of 21 polymorphic microsatellite markers for the barren-ground shrew, Sorex ugyunak (Mammalia: Sorcidae), through next-generation sequencing, and cross-species amplification in the masked shrew, S. cinereus - S. A. Sonsthagen; G. K. Sage; M. Fowler; A. G. Hope; J. A. Cook; S. L. Talbot (Conservation Genetics Resources, 2013)

Potential effects of climate change on biological control systems: case studies from New Zealand - P. J. Gerard; J. R. F. Barringer; J. G. Charles; S. V. Fowler; J. M. Kean; C. B. Phillips; A. B. Tait; G. P. Walker (BioControl, 2013)

Species dynamics alter community diversity–biomass stability relationships - Mike S. Fowler; Jouni Laakso; Veijo Kaitala; Lasse Ruokolainen; Esa Ranta (Ecology Letters, 2012)
The relationship between community diversity and biomass variability remains a crucial ecological topic, with positive, negative and neutral diversity–stability relationships reported from empirical studies. Theory highlights the relative importance of Species–Species or Species–Environment interactions in driving diversity–stability patterns. Much previous work is based on an assumption of identical (stable) species‐level dynamics. We studied ecosystem models incorporating stable, cyclic and more complex species‐level dynamics, with either linear or non‐linear density dependence, within a locally stable community framework. Species composition varies with increasing diversity, interacting with the correlation of species' environmental responses to drive either positive or negative diversity–stability patterns, which theory based on communities with only stable species‐level dynamics fails to predict. Including different dynamics points to new mechanisms that drive the full range of diversity–biomass stability relationships in empirical systems where a wider range of dynamical behaviours are important.

Blockade of the brain histamine H3 receptor by JNJ-39220675: preclinical PET studies with [11C]GSK189254 in anesthetized baboon - Jean Logan; Nicholas I. Carruthers; Michael A. Letavic; Steven Sands; Xiaohui Jiang; Colleen Shea; Lisa Muench; Youwen Xu; Pauline Carter; Payton King; Joanna S. Fowler (Psychopharmacology, 2012)

Blue shark Prionace glauca fin‐to‐carcass‐mass ratios in Spain and implications for finning ban enforcement - J. Santana‐Garcon; S. Fordham; S. Fowler (Journal of Fish Biology, 2012)
This study examines the processing of fins from blue sharks Prionace glauca caught by the Spanish longline fleet and landed in Vigo, Spain, and implications of these practices for enforcing the E.U. ban on shark finning, which relies on a maximum fin‐to‐carcass‐mass ratio. Two major sources of variability in fin‐to‐carcass ratios are quantified and discussed: (1) the fin set (type and number of fins retained from each shark) and (2) the cutting method used to separate fins from carcasses. The significant differences in fin‐to‐carcass‐mass ratios between fin sets or cutting procedure demonstrates that the ratio limit is problematic and, conclusively, in order to facilitate proper enforcement, fishermen should be required to land all sharks with the fins still naturally attached to the bodies.

Methanogenic toluene metabolism: community structure and intermediates - S. Jane Fowler; Xiaoli Dong; Christoph W. Sensen; Joseph M. Suflita; Lisa M. Gieg (Environmental Microbiology, 2012)
Summary Toluene is a model compound used to study the anaerobic biotransformation of aromatic hydrocarbons. Reports indicate that toluene is transformed via fumarate addition to form benzylsuccinate or by unknown mechanisms to form hydroxylated intermediates under methanogenic conditions. We investigated the mechanism(s) of syntrophic toluene metabolism by a newly described methanogenic enrichment from a gas condensate‐contaminated aquifer. Pyrosequencing of 16S rDNA revealed that the culture was comprised mainly of Clostridiales . The predominant methanogens affiliated with the Methanomicrobiales . Methane production from toluene ranged from 72% to 79% of that stoichiometrically predicted. Isotope studies using 13 C 7 toluene showed that benzylsuccinate and benzoate transiently accumulated revealing that members of this consortium can catalyse fumarate addition and subsequent reactions. Detection of a BssA gene fragment in this culture further supported fumarate addition as a mechanism of toluene activation. Transient formation of cresols, benzylalcohol, hydroquinone and methylhydroquinone suggested alternative mechanism(s) for toluene metabolism. However, incubations of the consortium with 18 O‐H 2 O showed that the hydroxyl group in these metabolites did not originate from water and abiotic control experiments revealed abiotic formation of hydroxylated species due to reactions of toluene with sulfide and oxygen. Our results suggest that toluene is activated by fumarate addition, presumably by the dominant Clostridiales .

Effects of acute pramipexole on preference for gambling-like schedules of reinforcement in rats - Patrick S. Johnson; Gregory J. Madden; Adam T. Brewer; Jonathan W. Pinkston; Stephen C. Fowler (Psychopharmacology, 2011)

Epidemiology of influenza-associated hospitalization in adults, Toronto, 2007/8 - S. P. Kuster; S. Drews; K. Green; J. Blair; I. Davis; J. Downey; R. Fowler; K. Katz; S. Lapinsky; D. McRitchie; J. Pataki; J. Powis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

When can we distinguish between neutral and non‐neutral processes in community dynamics under ecological drift? - Lasse Ruokolainen; Esa Ranta; Veijo Kaitala; Mike S. Fowler (Ecology Letters, 2009)
Determining whether the composition of ecological communities (species presence and abundance), can be predicted from species demographic traits, rather than being a result of neutral drift, is a key ecological question. Here we compare the similarity of community composition, from different community assembly models run under identical environmental conditions, where interspecific competition is assumed to be either neutral or niche‐based. In both cases, species colonize a focal patch from a network of neighbouring patches in a metacommunity. We highlight the circumstances (rate and spatial scale of dispersal, and the relative importance of ecological drift) where commonly used community similarity metrics or species rank–abundance relationships are likely to give similar results, regardless of the underlying processes (neutral or non‐neural) driving species’ dynamics. As drift becomes more important in driving species abundances, deterministic niche structure has a smaller influence. Our ability to discriminate between different underlying processes driving community organization depends on the relative importance of different drift processes that operate on different spatial scales.

Cumulative solar irradiance and potential large-scale sea ice algae distribution off East Antarctica (30°E–150°E) - Ben Raymond; K. Meiners; C. W. Fowler; B. Pasquer; G. D. Williams; S. Nicol (Polar Biology, 2009)

Methyl-donor nutrients inhibit breast cancer cell growth - Chung S. Park; Kyongshin Cho; Dong R. Bae; Nam E. Joo; Hyung H. Kim; Lawrence Mabasa; Andrea W. Fowler (In Vitro Cellular & Developmental Biology - Animal, 2008)

Candida infective endocarditis - J. W. Baddley; D. K. Benjamin; M. Patel; J. Miró; E. Athan; B. Barsic; E. Bouza; L. Clara; T. Elliott; Z. Kanafani; J. Klein; S. Lerakis; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Linking climate change modelling to impacts studies: recent advances in downscaling techniques for hydrological modelling - H. J. Fowler; S. Blenkinsop; C. Tebaldi (International Journal of Climatology, 2007)
There is now a large published literature on the strengths and weaknesses of downscaling methods for different climatic variables, in different regions and seasons. However, little attention is given to the choice of downscaling method when examining the impacts of climate change on hydrological systems. This review paper assesses the current downscaling literature, examining new developments in the downscaling field specifically for hydrological impacts. Sections focus on the downscaling concept; new methods; comparative methodological studies; the modelling of extremes; and the application to hydrological impacts. Consideration is then given to new developments in climate scenario construction which may offer the most potential for advancement within the ‘downscaling for hydrological impacts’ community, such as probabilistic modelling, pattern scaling and downscaling of multiple variables and suggests ways that they can be merged with downscaling techniques in a probabilistic climate change scenario framework to assess the uncertainties associated with future projections. Within hydrological impact studies there is still little consideration given to applied research; how the results can be best used to enable stakeholders and managers to make informed, robust decisions on adaptation and mitigation strategies in the face of many uncertainties about the future. It is suggested that there is a need for a move away from comparison studies into the provision of decision‐making tools for planning and management that are robust to future uncertainties; with examination and understanding of uncertainties within the modelling system. Copyright © 2007 Royal Meteorological Society

Changes in European drought characteristics projected by the PRUDENCE regional climate models - S. Blenkinsop; H. J. Fowler (International Journal of Climatology, 2007)
One of the key features of global climate change will be perturbations to the hydrological regime across Europe. To date, assessments of the impacts of future change have generally used results from only one climate model, thus underestimating the range of possible change projected by different climate models. Here, the skill of six regional climate models (RCMs) in reproducing the mean precipitation for the 1961–1990 period for six catchments across Europe is compared and their projections of changes in future precipitation are assessed. A simple drought index based on monthly precipitation anomalies is also described and used to assess the models. Considerable variation in model skill in reproducing monthly mean precipitation and drought statistics is observed, with model errors in the reproduction of drought events independent of those for the mean, suggesting that the models have difficulties in reproducing the observed persistence of low monthly rainfall totals. In broad terms, the models indicate decreases in summer and increases in winter precipitation across Europe. On the regional scales required for impacts analysis, considerable model uncertainty is demonstrated for future projections, particularly for drought frequency. Although increases in the frequency of long‐duration droughts are identified for catchments in southern Europe, the magnitude of this change is not certain. In contrast, for a catchment in northern England, such events are likely to become less frequent. For shorter‐duration droughts, future changes encompass the direction of change. For stakeholders in each of the regions, these changes and uncertainties pose different challenges for the management of water resources. For the scientific community, the challenge raised is how to incorporate this uncertainty in climate change projections in a way that allows those groups to make informed decisions based on model projections. It is suggested that probabilistic scenarios for specific hydrological impacts offer considerable potential to achieve this. Copyright © 2007 Royal Meteorological Society

Simple laboratory tests of ecological theories: What we can learn from them, and when we should be cautious - Mike S. Fowler; Lasse Ruokolainen (Journal of Biosciences, 2006)

Prosthetic valve endocarditis due to coagulase-negative staphylococci: findings from the International Collaboration on Endocarditis Merged Database - T. Lalani; Z. A. Kanafani; V. H. Chu; L. Moore; G. R. Corey; P. Pappas; C. W. Woods; C. H. Cabell; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; C. Chirouze; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Enterococcal prosthetic valve infective endocarditis: report of 45 episodes from the International Collaboration on Endocarditis-merged database - D. J. Anderson; L. Olaison; J. R. McDonald; J. M. Miro; B. Hoen; C. Selton-Suty; T. Doco-Lecompte; E. Abrutyn; G. Habib; S. Eykyn; P. A. Pappas; V. G. Fowler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Use of Radiotracer Techniques to Study Subcellular Distribution of Metals and Radionuclides in Bivalves from the Noumea Lagoon, New Calendonia - M. Metian; L. Hédouin; C. Barbot; J.-L. Teyssié; S. W. Fowler; F. Goudard; P. Bustamante; J.-P. Durand; J. Piéri; M. Warnau (Bulletin of Environmental Contamination and Toxicology, 2005)

Effects of combined lamotrigine and valproate on basal and stimulated extracellular amino acids and monoamines in the hippocampus of freely moving rats - Shagufta Ahmad; Leslie J. Fowler; Peter S. Whitton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Molecular and morphological analyses of the cuttlefish Sepia apama indicate a complex population structure - K. S. Kassahn; S. C. Donnellan; A. J. Fowler; K. C. Hall; M. Adams; P. W. Shaw (Marine Biology, 2003)

Hypervariability of the membrane-associated mucin and cancer marker MUC1 - Joanna C. Fowler; Ana S. Teixeira; Lynne E. Vinall; Dallas M. Swallow (Human Genetics, 2003)

Regulatory role of nitric oxide over hippocampal 5-HT release in vivo - Joanna Segieth; Brian Pearce; Leslie Fowler; Peter S. Whitton (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Oxidation of atmospheric methane in Northern European soils, comparison with other ecosystems, and uncertainties in the global terrestrial sink - K. A. Smith; K. E. Dobbie; B. C. Ball; L. R. Bakken; B. K. Sitaula; S. Hansen; R. Brumme; W. Borken; S. Christensen; A. Priemé; D. Fowler; J. A. Macdonald; et al. (Global Change Biology, 2000)
Summary This paper reports the range and statistical distribution of oxidation rates of atmospheric CH 4 in soils found in Northern Europe in an international study, and compares them with published data for various other ecosystems. It reassesses the size, and the uncertainty in, the global terrestrial CH 4 sink, and examines the effect of land‐use change and other factors on the oxidation rate. Only soils with a very high water table were sources of CH 4 ; all others were sinks. Oxidation rates varied from 1 to nearly 200 μg CH 4 m −2 h −1 ; annual rates for sites measured for ≥1 y were 0.1–9.1 kg CH 4 ha −1 y −1 , with a log‐normal distribution (log‐mean ≈ 1.6 kg CH 4 ha −1 y −1 ). Conversion of natural soils to agriculture reduced oxidation rates by two‐thirds –‐ closely similar to results reported for other regions. N inputs also decreased oxidation rates. Full recovery of rates after these disturbances takes > 100 y. Soil bulk density, water content and gas diffusivity had major impacts on oxidation rates. Trends were similar to those derived from other published work. Increasing acidity reduced oxidation, partially but not wholly explained by poor diffusion through litter layers which did not themselves contribute to the oxidation. The effect of temperature was small, attributed to substrate limitation and low atmospheric concentration. Analysis of all available data for CH 4 oxidation rates in situ showed similar log‐normal distributions to those obtained for our results, with generally little difference between different natural ecosystems, or between short‐and longer‐term studies. The overall global terrestrial sink was estimated at 29 Tg CH 4 y −1 , close to the current IPCC assessment, but with a much wider uncertainty range (7 to > 100 Tg CH 4 y −1 ). Little or no information is available for many major ecosystems; these should receive high priority in future research.

Behavioral tolerance to the force differentiation effects of diazepam and midazolam in rats - S. E. Bowen; S. C. Fowler; J. A. Stanford; M. J. Kallman (Psychopharmacology, 2000)

CHARACTERIZATION OF JOK-1, A HUMAN GASTRIC EPITHELIAL CELL LINE - N. OKAYAMA; M. R. FOWLER; S. R. JENNINGS; P. PATEL; R. SPECIAN; B. ALEXANDER; T. H. JACKSON; T. OSHIMA; K. SHANNON; J. S. ALEXANDER (In Vitro Cellular & Developmental Biology - Animal, 2000)

Minimal requirements for in vitro reconstitution of the structural subunit of light-harvesting complexes of photosynthetic bacteria - John B. Todd; Paul A. Recchia; Pamela S. Parkes-Loach; John D. Olsen; Gregory J. S. Fowler; Peter McGlynn; C. Neil Hunter; Paul A. Loach (Photosynthesis Research, 1999)

Identification of a highly conserved sequence at the N-terminus of the epithelial Na+ channel α subunit involved in gating - S. Gründer; N. Fowler Jaeger; I. Gautschi; L. Schild; B.C. Rossier (Pflügers Archiv - European Journal of Physiology, 1999)

Identification of a highly conserved sequence at the N-terminus of the epithelial Na + channel α subunit involved in gating - S. Gründer; N. Fowler Jaeger; I. Gautschi; L. Schild; B.C. Rossier (Pflügers Archiv - European Journal of Physiology, 1999)

Dopamine-transporter occupancy after intravenous doses of cocaine and methylphenidate in mice and humans - S. J. Gatley; Nora D. Volkow; Andrew N. Gifford; Joanna S. Fowler; Stephen L. Dewey; Yu-Shin Ding; Jean Logan (Psychopharmacology, 1999)

Phylogeographic differentiation in the mitochondrial control region in the koala, Phascolarctos cinereus (Goldfuss 1817) - Bronwyn A. Houlden; Brian H. Costello; Deirdre Sharkey; Elizabeth V. Fowler; Alistair Melzer; William Ellis; Frank Carrick; Peter R. Baverstock; Martin S. Elphinstone (Molecular Ecology, 1999)
The koala, Phascolarctos cinereus , is a geographically widespread species endemic to Australia, with three currently recognized subspecies: P.c. adustus , P.c. cinereus , and P.c. victor . Intraspecific variation in the mitochondrial DNA (mtDNA) control region was examined in over 200 animals from 16 representative populations throughout the species’ range. Eighteen different haplotypes were defined in the ≈ 860 bp mtDNA control region, as determined by heteroduplex analysis/temperature gradient gel electrophoresis (HDA/TGGE). Any single population typically possessed only one or two haplotypes yielding an average within‐population haplotypic diversity of 0.180 ± 0.003, and nucleotide diversity of 0.16%. Overall, mtDNA control region sequence diversity between populations averaged 0.67%, and ranged from 0% to 1.56%. Nucleotide divergence between populations averaged 0.51%, and ranged from 0% to 1.53%. Neighbour‐joining methods revealed limited phylogenetic distinction between geographically distant populations of koalas, and tentative support for a single evolutionarily significant unit (ESU). This is consistent with previous suggestions that the morphological differences formalized by subspecific taxonomy may be interpreted as clinal variation. Significant differentiation in mtDNA‐haplotype frequencies between localities suggested that little gene flow currently exists among populations. When combined with microsatellite analysis, which has revealed substantial differentiation among koala populations, we conclude that the appropriate short‐term management unit (MU) for koalas is the local population.

Haloperidol, raclopride, and eticlopride induce microcatalepsy during operant performance in rats, but clozapine and SCH 23390 do not - S. C. Fowler; Jiing-Ren Liou (Psychopharmacology, 1998)

Similarities and differences between the subchronic and withdrawal effects of clozapine and olanzapine on forelimb force steadiness - John A. Stanford; S. C. Fowler (Psychopharmacology, 1997)

Chiral drugs: comparison of the pharmacokinetics of [ 11 C] d-threo and l-threo -methylphenidate in the human and baboon brain - Y.-S. Ding; J. S. Fowler; N. D. Volkow; S. L. Dewey; G.-J. Wang; J. Logan; S. J. Gatley; N. Pappas (Psychopharmacology, 1997)

Integration of trinucleotide microsatellites into a linkage map of Citrus - J. M. H. Kijas; M. R. Thomas; J. C. S. Fowler; M. L. Roose (Theoretical and Applied Genetics, 1997)

Non-neutralizing monoclonal antibodies to a trypsin-sensitive site on the major glycoprotein of rotavirus which discriminate between virus serotypes - Barbara S. Coulson; K. J. Fowler; J. R. White; R. G. H. Cotton (Archives of Virology, 1987)

Transformation of rabbit arterial smooth muscle cells with Simian virus 40 - M. Nachtigal; P. Greenspan; L. Terracio; S. D. Fowler (Archives of Virology, 1987)